2019
DOI: 10.3390/toxins11020126
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Depletion from Plasma Membranes of Human Airway Epithelial Cells Completely Abrogates the Deleterious Actions of S. aureus Alpha-Toxin

Abstract: Interaction of Staphylococcus aureus alpha-toxin (hemolysin A, Hla) with eukaryotic cell membranes is mediated by proteinaceous receptors and certain lipid domains in host cell plasma membranes. Hla is secreted as a 33 kDa monomer that forms heptameric transmembrane pores whose action compromises maintenance of cell shape and epithelial tightness. It is not exactly known whether certain membrane lipid domains of host cells facilitate adhesion of Ha monomers, oligomerization, or pore formation. We used sphingom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Alterations in the normal activities of SM-cycle enzymes have been linked to many central nervous system-related pathologies such as Alzheimer's, Parkinson's, ischemia/hypoxia, depression, schizophrenia or Niemann-Pick diseases 19 .Specific SL functions have often been characterized in cells with decreased amounts of SL, using either SL-degrading enzymes (e.g. sphingomyelinases or ceramidases) 20 , or specific enzyme inhibitors 15,[21][22][23] , of which the SPT inhibitor myriocin is a good example [24][25][26][27] . Procedures to decrease the SL contents of cells constitute good tools to determine their potential functions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the normal activities of SM-cycle enzymes have been linked to many central nervous system-related pathologies such as Alzheimer's, Parkinson's, ischemia/hypoxia, depression, schizophrenia or Niemann-Pick diseases 19 .Specific SL functions have often been characterized in cells with decreased amounts of SL, using either SL-degrading enzymes (e.g. sphingomyelinases or ceramidases) 20 , or specific enzyme inhibitors 15,[21][22][23] , of which the SPT inhibitor myriocin is a good example [24][25][26][27] . Procedures to decrease the SL contents of cells constitute good tools to determine their potential functions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…A ppiB mutant that no longer encodes one of the PPIases produced less alpha-toxin and phenol-soluble modulins (PSMs) compared to the unmutated parent strain. A change in the host cell membrane that affected alpha-toxin activity was explored in the work done by Ziesemer et al [11]. When sphingomyelinase was used to pre-treat airway epithelial cells, alpha-toxin heptamer formation was blocked, which led to a loss of transmembrane pore formation.…”
mentioning
confidence: 99%
“…α-toxin is secreted by S. aureus as a monomer and is assembled as a heptameric protein complex after binding to non-specific lipid receptors (Schwiering et al, 2013; Ziesemer et al, 2019) or the metalloprotease ADAM10 (Wilke and Bubeck Wardenburg, 2010) on target membranes. Due to its small pore diameter, it was suggested that S. aureus α-toxin pores are only permeable for small cations, predominantly potassium (Harshman et al, 1989; Jonas et al, 1994), although the permeability of the plasma membrane for Ca 2+ and larger molecules such as ATP was also demonstrated (Jonas et al, 1994; Gierok et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ASM is a crucial factor for the conversion of sphingomyelin to ceramide in the extracellular leaflet of the injured plasma membrane (Andrews et al, 2014). Since this removal of plasma membrane sphingomyelin mediates resistance to α-toxin (Ziesemer et al, 2019) it is tempting to speculate that ASM release of injured mammalian cells do not only initiate plasma membrane repair mechanisms, but also may decrease membrane sensitivity against the toxin. In addition, α-toxin pores were found to be excreted, if cells were unable to remove the pore by proteolysis (Husmann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation